The Socio-demographic problems of the development of united territorial communities of the Eastern regions of Ukraine - Boichenko Elina; Vasilchuk Nataly (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
Taking into account the comprehensive decentralization reform in Ukraine, which began in 2014 and the ambiguity of the situation in the East of Ukraine, there is an increased interest in the study of decentralization processes in these regions. Since the process of unification of local communities involves, above all, taking into account the interests of the population, the authors decided to consider the socio demographic problems of local communities united by the example of the Donetsk region. The article substantiates the expediency of choosing as an example of the Liman City United Territorial Community. The dynamics of distribution of population by the communities of Donetsk region is presented. The dynamics of changes in the population of the Liman city UTC before and after the merger are analyzed. Revealed changes in the age structure of the population of the community and founded the main causes and consequences of these changes. In addition, it has been found that, contrary to changes in the territorial structure of the country, the existing form of submission of statistical information remains unaltered (statistics are provided in the traditional way, namely, in cities and rayons of the region), which in turn does not allow to trace all social and economic changes and requires an immediate reformatting of statistical forms.